Prenatal Spina Bifida Repair: A Survey of Current Practice in the United States - Stuti P. Garg, BA; Krish V. Shah; Marina Lentskevich, MD; Alice Yau, MD; Arun K. Gosain, MD, FACS (Plastic and Reconstructive Surgery, Global Open)
Background:. Prenatal myelomeningocele (MMC) repair offers significant benefits over traditional postnatal repair, as demonstrated by the Management of Myelomeningocele Study trial. We characterize the current specialist involvement in prenatal and postnatal MMC repair. Methods:. The top 50 US News Children’s Hospitals for Neonatology and Neurology/Neurosurgery were queried, resulting in 67 unique hospitals. Specialties involved in MMC repair were extracted via hospital websites and surveys. Results:. Among the 58 hospitals included, only 18 (31%) offered both prenatal and postnatal MMC repair, and the remaining 40 (69%) offered postnatal repair only. Of the 40 hospitals offering postnatal repair only, neurosurgeons (n = 38), orthopedic surgeons (n = 34), and urologists (n = 33) were most often included. Of the 18 hospitals with prenatal repair, neurosurgeons (n = 18) and maternal–fetal medicine specialists (n = 14) were most commonly involved. Prenatal teams had pediatric and fetal surgeons involved more often than postnatal teams (P = 0.011 and P = 0.035, respectively). Only 7 prenatal teams included fellowship-trained fetal surgeons. Teams led by fetal surgeons always included neurosurgeons (n = 7) and maternal–fetal medicine specialists (n = 7) and were least likely to include plastic surgeons (n = 1). Conclusions:. These data emphasize both the delayed adaptation of fetal repair of MMC by major children’s hospitals and lack of fellowship-trained specialists involved; only 31% of the major children’s hospitals offer prenatal repair of MMC, with only 39% of those hospitals being led by a fellowship-trained fetal surgeon. These data highlight the need for additional teams trained in prenatal MMC repair as well as the standardization of fetal surgery fellowships to allow for the development of prenatal repair teams.